Invited Article: A rigid coherent anti-Stokes Raman scattering endoscope with high resolution and a large field of view - Zirak, P.; Matz, G.; Messerschmidt, B.; Meyer, Tobias; Schmitt, Michael; Popp, J.; Uckermann, O.; Galli, Roberta; Kirsch, M.; Winterhalder, M. J.; Zumbusch, A. (APL Photonics, 2018)
Nonlinear optical endoscopy is an attractive technique for biomedical imaging since it promises to give access to high resolution imaging in vivo. Among the various techniques used for endoscopic contrast generation, coherent anti-Stokes Raman scattering (CARS) is especially interesting. CARS endoscopy allows molecule specific imaging of unlabeled samples. In this contribution, we describe the design, implementation, and experimental characterization of a rigid, compact CARS endoscope with a spatial resolution of 750 nm over a field of view of roughly 250 μm. Omission of the relay optics and use of a gradient index lens specifically designed for this application allow one to realize these specifications in an endoscopic unit which is 2.2 mm wide over a length of 187 mm, making clinical applications during surgical interventions possible. Multimodal use of the endoscope is demonstrated with images of samples with neurosurgical relevance.
CRIS-Team Scopus Importer:2023-04-20